Analysis of factors and motives affecting the wrong response to the change process in tourism organizations in the holy Karbala - A.Prof. Samir Khalil Ibrahim Shamto (Peerian Journals Publishing, 2024)
The research aims to identify the main factors and psychological and organizational motives that affect the incorrect response to change processes in tourism organizations, and to provide practical recommendations to improve change management in tourism organizations. The research contributes to developing literature on change management in tourism organizations, in addition to defining change, its importance and motives, as well as identifying the factors affecting the response to the change process. A questionnaire form was designed with two main axes, each axis included (6) questions, (120) forms were distributed, and (112) forms were validated. One of the most important field results was that the management of the tourism organization supports change in the competitive market, and that the employees’ attitude towards change in the organization is positive, thus ensuring that the administrations do not respond incorrectly to the change process. We recommended that the administrations of tourism organizations focus on the participation of employees with their opinions and suggestions in the change process
Keywords: employees; participation; identifying